Docetaxel based chemotherapy in the treatment of patients with castration resistant prostate cancer [Quimioterapia basada en docetaxel en el tratamiento de pacientes con cáncer de prostata resistente a la castración] - (:unkn) unknown (Elsevier Ltd, 2014)
Introduction: Docetaxel administered every 3- weeks is the standart treatment of castrationresistant prostate cancer (CRPC) but it is associated with dose limiting toxicities. We analyzedthe efficacy and tolerability of 3- weekly and weekly docetaxel in a Turkish cohort of CRPCpatients with a special emphasis on the elderly patients.Materials and methods: A retrospective analyses of 45 patients who received either 3- weeklyor weekly docetaxel in a single urologic oncology clinic was performed. Response to therapy,toxicity and overall survival rates were evaluated.Results: The mean age of patients was 70.0 (± 8.8) years. Complete or partial PSA response wasobtained in 45% of patients. The median overall survival was 20,0 months (SE 6.46; 95% CI 7,3-32,6). Absence of metastasis, time to CRPC > 10 months, DP 75 mg/m2 once every three weeksand PSA < 50% at the end of the third cycle were associated with better overall survival. Therewas no significant survival difference between the patients aged 75 or older versus youngerones. The most common hematological toxicity was leukopenia which was dose limiting in onlyone patient.Conclusion: Administration of standart 3-weekly docetaxel is well tolerated in this relativelyold cohort of Turkish CRPC patients and weekly administration can be a reasonable alternativein frail patients not only to prolong survival but also to palliate disease symptoms. © 2013 AEU. Published by Elsevier Espaa, S.L.U. All rights reserved.
Keywords: Castration resistant; Chemotherapy; Docetaxel; Prostate cancer; Survival; Toxicity